2014
DOI: 10.1186/2047-783x-19-34
|View full text |Cite
|
Sign up to set email alerts
|

Combination of BCL11A siRNA with vincristine increases the apoptosis of SUDHL6 cells

Abstract: BackgroundB cell chronic lymphocytic leukemia/lymphoma 11 A (BCL11A) is associated with human B cell malignancy initiation. Our previous study has shown that downregulation of BCL11A mRNA by small interfering RNA (siRNA) is capable of inducing apoptosis in the SUDHL6 cell line. To further explore the effects of BCL11A siRNA on the enhanced cytotoxicity of a chemotherapeutic drug, we investigated the effects of BCL11A siRNA combined with vincristine (VCR) on SUDHL6 cell proliferation and apoptosis.MethodsChemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…On the basis of previous results, in TNBC cells, disrupting BCL11A expression significantly reduced cell proliferation and invasion. Additionally, gene expression profiling of BCL11A siRNA-treated SUDHL6 cells proved that BCL11A could be associated with the signaling network of cell cycle (22). However, the present data did not indicate a relationship between BCL11A and cell cycle in TNBC.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…On the basis of previous results, in TNBC cells, disrupting BCL11A expression significantly reduced cell proliferation and invasion. Additionally, gene expression profiling of BCL11A siRNA-treated SUDHL6 cells proved that BCL11A could be associated with the signaling network of cell cycle (22). However, the present data did not indicate a relationship between BCL11A and cell cycle in TNBC.…”
Section: Discussioncontrasting
confidence: 77%
“…Notably, BCL11A may also promote stemness in breast cancer cells by inducing Wnt/β-catenin signaling (21). BCL11A activation is associated with the induction of numerous carcinogenic signaling pathways, and there is growing evidence to suggest that BCL11A downregulation inhibits tumorigenesis (22,23). However, the specific functions of BCL11A and the underlying mechanism of its involvement in TNBC have not been fully clarified.…”
Section: Bcl11a Confers Cell Invasion and Migration In Androgenmentioning
confidence: 99%
“…Taking into account the above data, the description of vincristine antitumour potential varies according to concentration, exposure time, and the number of cells in the mitosis phase during the exposure period . Researchers using the drug for solid tumour treatment, and other cell lines of different TVT, also described high percentages of apoptosis . In addition, Shi et al , when comparing various cancer cell lines observed that death, as a response to antimitotic treatment, varies widely …”
Section: Discussionmentioning
confidence: 99%
“…Although the expression pattern of Bcl11a gene has been described in B‐cell lymphomas and B‐CLL, little is known about the expression character of Bcl11a gene in B‐ALL. In this study, Bcl11a and Mdm2, Pten mRNA expression in B‐ALL was determined by real‐time quantitative PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, our previous results have shown that a broad range of genes including murine double minute 2 ( Mdm2 ) and phosphorate and tension homolog ( Pten ) were altered by analyzing the global gene expression profile in the diffuse large B‐cell lymphoma cell line SUDHL6 after Bcl11a downregulation . Our previous study has also showed that Bcl11a was related to apoptosis and proliferation of B lymphoma cells …”
Section: Introductionmentioning
confidence: 99%